Current and future trends in the teaching of direct posterior resin composites in Malaysian dental schools: a cross-sectional study. (July 2021) - Sidhu, Preena; Sultan, Omer Sheriff; Math, Swarna Yerebairapura; Malik, Normaliza Ab; Wilson, Nairn H.F.; Lynch, Christopher D.; Blum, Igor R.; Daood, Umer
Abstract: Objective: To investigate the current and future teaching of posterior composite restorations in undergraduate curricula in Malaysian dental schools. Methods: A 24-item validated questionnaire including closed and open questions on the teaching of posterior composites was emailed to faculty members in all 13 Dental Schools in Malaysia. Responses were compiled on Excel and analysed. Results: All 13 dental schools responded to the survey yielding a 100 % response. All schools indicated the use of posterior composites for 2- and 3-surface cavities in premolars and molars. The didactic teaching time devoted to composites was greater than for amalgam (38 h vs 29 h). Clinically, most posterior restorations placed by students were composites (average 74.1 %, range 10 %–100 %); the remaining 25.9 % were amalgams (range, 0 %–50 %). Slot-type cavities were the preparation techniques most commonly taught (n = 11, 84.6 %). The use of rubber dam for moisture control was mandatory in most schools (n = 11, 84.6 %). History of adverse reaction to composites was found to be the most common contraindication to composite placement. The phase down of teaching and use of amalgam in Malaysia is expected to occur within the next six years. Conclusion: The trend to increase the teaching of posterior composites reported for other countries is confirmed by the findings from Malaysian dental schools. Notwithstanding this trend, the use of amalgam is still taught, and future studies are required to investigate the implications of the phase down of amalgam in favour of posterior composites. Clinical significance: Notwithstanding the increase in the teaching of posterior composites there is a pressing need to update and refine clinical guidelines for the teaching of posterior composites globally.